Influence of Molecular Geometry of Perylene Diimide Dimers and Polymers on Bulk Heterojunction Morphology Toward High‐Performance Nonfullerene Polymer Solar Cells. (24th July 2015) - Wu, Chen‐Hao; Chueh, Chu‐Chen; Xi, Yu‐Yin; Zhong, Hong‐Liang; Gao, Guang‐Peng; Wang, Zhao‐Hui; Pozzo, Lilo D.; Wen, Ten‐Chin; Jen, Alex K.‐Y.
Abstract : In this study, we investigate the influence of molecular geometry of the donor polymers and the perylene diimide dimers (di‐PDIs) on the bulk heterojunction (BHJ) morphology in the nonfullerene polymer solar cells (PSCs). The results reveal that the pseudo 2D conjugated poly[4, 8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)benzo[1, 2‐b;4, 5‐b′]dithiophene‐2, 6‐diyl‐alt‐(4‐(2‐ethylhexyl)‐3‐fluorothieno[3, 4‐b]thiophene‐)‐2‐carboxylate‐2‐6‐diyl)] (PTB7‐Th) has better miscibility with both bay‐linked di‐PDI (B‐di‐PDI) and hydrazine‐linked di‐PDI (H‐di‐PDI) compared to its 1D analog, poly[[4, 8‐bis[(2‐ethylhexyl)oxy]benzo[1, 2‐b:4, 5‐b′]dithiophene‐2, 6‐diyl][3‐fluoro‐2‐[(2‐ethylhexyl)carbonyl]thieno[3, 4‐b]thiophenediyl]] (PTB7), to facilitate more efficient exciton dissociation in the BHJ films. However, the face‐on oriented π–π stacking of PTB7‐Th is severely disrupted by the B‐di‐PDI due to its more flexible structure. On the contrary, the face‐on oriented π–π stacking is only slightly disrupted by the H‐di‐PDI, which has a more rigid structure to provide suitable percolation pathways for charge transport. As a result, a very high power conversion efficiency (PCE) of 6.41% is achieved in the PTB7‐Th:H‐di‐PDI derived device. This study shows that it is critical to pair suitable polymer donor and di‐PDI‐based acceptor to obtain proper BHJ morphology for achieving high PCE in the nonfullerene PSCs. Abstract : Suitable selection of perylene diimide dimer (di‐PDI)‐based acceptors and polymer donors is essential to optimize the bulk heterojunction morphology. When blended with the 2D polymer, PTB7‐Th, the rigidly hydrazine‐linked di‐PDI affords the recorded power conversion efficiency of 6.4% due to excellent miscibility for efficient exciton dissociation and appropriate percolation pathways for charge transport.